ANALYSIS OF TWITTER USER INTERACTIONS USING SOCIAL NETWORKS AT PAYDAY SALE EVENTS ON THE MARKETPLACE - Nur Chamila, Ayuni; Ambarwati, Rita; Sari, Dewi Komala (Institut Teknologi dan Bisnis Asia Malang, 2024)
The goal of this study was to ascertain the marketplace companies' commitment to implementing SCRM on social media and to identify patterns of engagement, interaction, and communication between Twitter users and the marketplaces Shopee, Tokopedia, and Lazada that emerged on social media at payday sale events. The Social Network Analysis (SNA) approach is being used in this qualitative study. Twitter users in Indonesia are the focus of this study. The users of Tokopedia, Shopee, and Lazada are the research population. Dictionary, Notepad++, Wordij, and Gephi are supporting tools used in this study together with Jupyter Notebook. The Shopee Marketplace is superior and performs better, according to an analysis of network features. According to the analysis, the Shopee marketplace has a broader network. According to this study, many consumers utilize Shopee as their online shopping destination, particularly during payday sale events when each marketplace offers alluring discounts and free delivery.